2012
DOI: 10.4238/2012.october.17.7
|View full text |Cite
|
Sign up to set email alerts
|

Transferability and characterization of simple sequence repeat markers from Anacardium occidentale to A. humile (Anacardiaceae)

Abstract: ABSTRACT. Use of molecular markers can be limited by the high cost and extensive time required for their development. Transfer of simple sequence repeat (SSR) markers reduces the cost and time limitations and has allowed the use of these markers in a larger number of species. We tested 11 SSR markers previously developed for Anacardium occidentale on A. humile. The 11 loci were successfully amplified in A. humile. All loci were polymorphic and generated a mean of 5.4 alleles per locus. The observed heterozygos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(46 reference statements)
0
7
0
1
Order By: Relevance
“…Six microsatellite loci previously developed for A. occidentale (Croxford et al, 2006) and transferred to A. humile (Cota et al, 2012) were used in population genetic analyses ( Table 2). The 15-µL reactions, containing 1X buffer (10 mM Tris-HCl, pH 8.4, 50 mM KCl), 0.7 μM of each primer, 250 μM of each dNTP, 1 U Taq DNA polymerase, 0.25 mg BSA, 1.0 to 1.6 mM MgCl 2 , 1.25 to 3% formamide, and 9 ng DNA were PCR-amplified using a Veriti thermocycler (Applied Biosystems).…”
Section: Sampling Dna Extraction and Microsatellite Analysismentioning
confidence: 99%
“…Six microsatellite loci previously developed for A. occidentale (Croxford et al, 2006) and transferred to A. humile (Cota et al, 2012) were used in population genetic analyses ( Table 2). The 15-µL reactions, containing 1X buffer (10 mM Tris-HCl, pH 8.4, 50 mM KCl), 0.7 μM of each primer, 250 μM of each dNTP, 1 U Taq DNA polymerase, 0.25 mg BSA, 1.0 to 1.6 mM MgCl 2 , 1.25 to 3% formamide, and 9 ng DNA were PCR-amplified using a Veriti thermocycler (Applied Biosystems).…”
Section: Sampling Dna Extraction and Microsatellite Analysismentioning
confidence: 99%
“…No entanto, diante da carên-cia de informações genéticas sobre esta espécie, alguns estudos vêm sendo desenvolvidos, como os de , que estudaram polimorfismo genético entre populações naturais de A. humile; de Carvalho et al (2012), que analisaram a variabilidade genética da espé-cie com técnica molecular de marcadores RAPD, indicando grande variabilidade genética entre acessos e os estudos de Cota et al (2012) e Soares et al (2013), em que marcadores microssatélites foram transferidos da espécie Anarcadium occidentale para o A. humile, obtendo loci altamente polimórficos que servirão como ferramentas robustas nas análises genéticas de populações desta espécie.…”
Section: Introductionunclassified
“…Transferability of microsatellite primers for species within the same genus has been reported previously, such as in Euterpe, E. edulis to E. oleracea, the 7 loci tested presenting 100% success (Oliveira et al, 2010) and Anacardium, A. occidentale, to A. humile, with transferability of all 11 loci analyzed (Cota et al, 2012). Furthermore, rates of polymorphism higher than those observed in this study were obtained by Ince et al (2010a), who detected polymorphisms between the species C. annuum L. and C. frutescens L., with 34 microsatellite primer pairs among the 45 pairs tested.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have shown high transferability of SSR markers for species within the same genus, including Cucumis (Ritschel et al, 2004), Arachis (Bravo et al, 2006), and even for Capsicum (Yi et al, 2006;Nagy et al, 2007;Ince et al, 2010a). However, the success of this approach depends on the species considered, as the probability of obtaining transferability is inversely proportional to the evolutionary distance among them (Cota et al, 2012).…”
Section: Introductionmentioning
confidence: 99%